the influence PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KEANDALAN PELAPORAN KEUANGAN (Studi Pada Bank Papua Kantor Cabang Manokwari) - camelia lusandri numberi; Marlina Malino; Simson Werimon; Alvany Theresia Wanma (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2023)
The objectives of this research is to find out the impact of the human resource capacity, the utilization of information technology and the system of accounting internal control to the reliability of financial reporting (Case Study at the Main Branch Office of Papua Bank in Manokwari). Population in this research is all of the employees of the Main Branch Office of Papua Bank in Manokwari that carry out accounting and financial function which is 35 people. The sampling technique used saturated sample technique (census). The data used is primary data taken directly from the the distributed questionnaires. The results shows that the human resource capacity, the utilization of information technology and the internal control of accounting have a postive and significant impact on the reliability of financial reporting at Bank Papua Main Branch Office of Manokwari). Therefore, the human resource capacity, the utilization of information technology and the internal control of accounting determine the reliablity of financial reporting.